The tumor-targeted CD40 agonist CEA-CD40 promotes T cell priming via a dual mode of action by increasing antigen delivery to dendritic cells and enhancing their activation. Issue 3 (15th March 2022) - Sum, Eva; Rapp, Moritz; Dürr, Harald; Mazumdar, Alekhya; Romero, Pedro J; Trumpfheller, Christine; Umaña, Pablo
Abstract : Tumor-targeted CD40 agonism represents an attractive strategy for cancer immunotherapy (CIT) as it promotes dendritic cell (DC) activation and concomitant tumor-specific T cell priming without causing systemic side effects. We developed the bispecific CD40 agonistic antibody CEA-CD40, which triggers CD40 stimulation exclusively in the presence of carcinoembryonic antigen (CEA), a glycoprotein specifically expressed on tumor cells. In this study, we demonstrate that CEA-CD40 can enable potent in vitro DC activation and consecutive T cell cross-priming in a CEA-specific manner. Furthermore, we provide evidence that CEA-CD40 increases colocalization of CEA + tumor material and DCs. Using CEA + tumor-derived extracellular vesicles (EVs), which are known to be an excellent tumor antigen source, we show that CEA-CD40 mediates delivery of CEA + EVs to DCs. Importantly, our data indicates that this fosters acquisition of tumor EV major histocompatibility complex I/peptide complexes by DCs, consequently improving CD8 + T cell priming against EV-associated antigen in vitro. Thus, we provide mechanistic evidence for a dual mode of action of CEA-CD40 for CIT: we suggest that CEA-CD40 has the potential to activate DCs and in addition can promote their loading with tumor antigen derived from EVs to trigger tumor-specific T cell cross-priming.